Community Perceptions Towards Temporary Waste Storage Place and the Effectiveness of Waste Management in Malang City - Samin Samin; Sunarto Sunarto (School of Postgraduate Studies, Diponegoro Univer, 2024)
Waste generated due to population density in Malang City causes the need for optimal and planned temporary waste storage place (TWSP) that can reduce waste properly so as not to endanger health. This qualitative research aimed to find out and analyze people's perceptions of TWSP and the effectiveness of TWSP management in Malang City. The subjects of this study were the community and officers from 15 polling stations in Malang City. Data analysis used quantitative descriptive analysis. The results showed that the community had a positive perception of TWSP in Malang City and had knowledge regarding TWSP technical criteria such as location, TWSP capacity, equipment and ease of access, and aesthetics of the place. Regarding TWSP management effectiveness, Malang City is not yet optimal and not effective in waste management at TWSP. Inadequate location, lack of waste grouping, inadequate equipment, and the absence of waste processing into other materials such as compost are obstacles to the absence of waste processing and inefficient waste transportation in almost all TWSP.